Between agora and shopping mall - Josef Falkinger (Institute for the Study of Labor (IZA), 2008)
Advertisements provide consumers with knowledge about private products, whereas political information is required to provide voters with knowledge of public issues. Modern information technologies and globalization are increasing the exposure of individuals to information. Goods advertising is competing with political information for people's attention. This paper presents a politico-economic equilibrium model in which the tension between private and public agendas can be analysed. It is shown that in an information-rich society, international goods market integration tends to reduce the quality of public policy. Complementing economic integration with political integration can increase the gains from globalisation, though not in all cases.
urn:nbn:de:101:1-20080605194
Keywords: D83; 330; Globalisation; agenda-setting; information-rich societies; scarcity of attention; advertising; Werbung; Staatliche Information; Wettbewerb; Wahrnehmung; Medienverhalten; Public Choice; Allgemeines Gleichgewicht; Globalisierung; Informationsgesellschaft; Theorie